Geology and Geochemistry of Intrusion around Mayo-Kole Area within Adamawa Massif, Northeastern Nigeria - Ahmed, H. A. (IJRDO-Journal of Applied Science, 2017)
The Intrusion in Mayo-Kole and environs belongs to the crystalline basement rocks of the northern part of Adamawa Massif, Northeastern Nigeria. Most of the work done within the study area was on regional scale, no detailed work has been done on the geochemistry of the area. Previous studies have focused on engineering geology and geotechnical assessment of gully sites in the area. The area under study consists of granite, granodiorite, diorite and gabbro. This intrusion is characterized by high-K calc-alkaline and classified as metaluminous and peraluminous. Field investigations along with petrographic and geochemical studies indicate that the series of intrusion in the study area are derived from a common magma source as a result of fractional crystallization. The geodynamic setting of this intrusion is classified as pre-plate collision setting derived from mantle fractionates, which was formed during the Pan African thermotectonic events in the Nigerian Basement Complex. The tectonic structures in the study area trend mostly NE – SW and subordinately NW-SE and N-S, conforming with the regional deformational structures which occurred during the Pan African thermotectonic events in the Nigerian basement.